Transformasi Wilayah Kepulauan di Metropolitan Jakarta - Hafidz Wibisono; Azis Musthofa; Muhammad Eka Kusuma; Indrawan Haryanto (Department of Urban and Regional Planning, Diponegoro University, 2019)
Jakarta Metropolitan Area (Jakarta, Bogor, Depok, Tangerang, South Tangerang and Bekasi) has experienced rapid development, especially in the past 30 years. Jakarta Metropolitan Development has triggered conversion of agricultural land to urban areas and the development of settlements, especially in the periphery areas. Numerous studies have discussed how the process of transformation of peripheral areas located in the mainland region. However, there is still limited research which discusses the transformation of Kepulauan Seribu Regency, as one of the periphery of Jakarta metropolitan. This study aims to identify the process of regional transformation in Kepulauan Seribu Regency and elaborating on its role of as a periphery of Jakarta Metropolitan Area as well as limitations of regional development in Kepulauan Seribu Regency as an archipelagic region. The study used qualitative method by using a secondary data and literature studies. This study found that the transformation process in Kepulauan Seribu Regency has not occurred significantly, but an indication of the transformation of Kepulauan Seribu Regency as a tourism-based trade and service area has been identified. On the other hand, limited access and land oriented policies are some of the things that could make the transformation of this area would not as rapid as other periphery in the mainland.